The essential guide to selecting and using core reading programs (International Reading Association, 2010)
This groundbreaking, innovative resource is what every school using or planning to use a core reading program absolutely must have. This one-of-a-kind guide takes an objective look at the skills, texts, and assessments included in the most commonly used programs to first help you evaluate and select an effective program and then implement that program.